(untitled) (International journal of artificial intelligence, 2026)
Effective disinfection of the root canal system is a critical determinant of successful endodontic treatment. The complex anatomy of root canals, presence of microbial biofilms, and resistance of certain microorganisms significantly limit the effectiveness of conventional chemomechanical preparation. Despite advances in endodontic instrumentation, complete elimination of microorganisms using traditional irrigants remains challenging. Consequently, persistent infection remains one of the leading causes of endodontic treatment failure. In recent years, significant attention has been directed toward the development of novel antiseptic agents and the application of laser-assisted disinfection techniques. New-generation antiseptics aim to enhance antimicrobial efficacy while maintaining biocompatibility and minimizing cytotoxic effects. Laser therapy, on the other hand, offers a physical method of microbial inactivation through photothermal and photomechanical effects, potentially improving penetration into dentinal tubules and complex canal anatomy. The present study provides a comprehensive analysis of modern root canal disinfection methods, focusing on the comparative effectiveness of innovative antiseptics and laser-based technologies. Available experimental and clinical evidence suggests that the combined use of advanced chemical agents and laser therapy significantly improves microbial reduction and may enhance long-term endodontic outcomes.